Experimental and DFT generated Raman study of two bent-core monomeric liquid crystalline compounds. Issue 3 (19th February 2019) - Bhattacharjee, Debanjan; Mishra, Ramanuj; Dabrowski, Roman; Bhattacharjee, Ayon
ABSTRACT: The temperature dependence Raman spectra of two liquid crystalline compounds defined by the chemical formula of 3, 5-difluoro-4ʹ-(4-pentylcyclohexyl)-(1, 1ʹ-biphenyl)-4-carbonitrile and 3, 4, 5-trifluoro-4ʹ-(4-pentylcyclohexyl)-1, 1ʹ-biphenyl is being first reported in this study. These compounds are bent-core monomers and their bent nature has been verified by the Density Functional Theory (DFT). The temperature-dependent Raman spectroscopy has been widely used in understanding the effects of temperature-based phase transitions on the molecular vibrations. The same spectroscopic technique; helps to understand various phase transitions temperature in the liquid crystalline compounds (LC) and also their molecular arrangements during the phase transitions. This study has successfully revealed the nature of intermolecular interactions between the investigated compounds during the phase transitions and the correlation between the observed Raman spectra and the measurement temperature. The contributions of different types of chemical bonds in the investigated LC compounds to their recorded Raman spectra have also been discussed in detail. In predicting the observed Raman spectra, the theoretical Raman spectra obtained from the DFT calculation was used as a reliable tool. In the light of the calculated data, the peak position, line width, and integral intensity data for each band in the observed Raman spectra were reported. GRAPHICAL ABSTRACT: